Independent tps dose verification for photon beam shaped with multileaf collimator: evidence from single-institution study - Ab Rahim, Rohaizah Mohamad; Ahmad Fadzil, Muhammad Safwan; Azmi, Nor Aniza; Sabarudin, Akmal; Mohd Saparudin, Abdul Khaliq; Dollah, Mohd Taufik; Min, Ung Ngie; Mohd Noor, Noramaliza (Elsevier BV, 2023)
This study was conducted to initiate the IAEA's fourth sequential of remote dosimetry auditing steps, which involves the treatment planning system (TPS) dose verification for photon beams shaped with multileaf collimators (MLC). A dosimetry package containing plastic capsules, a TLD holder, an instruction booklet, and datasheets were mailed to the radiotherapy center. Plastic capsules filled with TLD-100 were prepared for irradiation to check the dose variation with field size and shape for a range of MLC-shaped regular and irregular fields, including wedged fields. Each capsule was irradiated to 2 Gy of absorbed dose utilizing 6 MV and 10 MV beams. The dose calculated by the TPS (DTPS) was compared to the dose measured by the ionization chamber (DIC) and TLD-100 (DTLD). RESULTS All 14 measurements point within ±5 of the TPS dose. For 6 MV and 10 MV beams, the percentage deviation between DTPS to DIC and DTLD was between 0.10 to 3.75 and 0.05 to 4.40, respectively. The mean ratio of DIC/DTPS exposed to 6 MV and 10 MV beams was 1.003 ± 0.004 and 1.007 ± 0.014, respectively, whereas the mean ratio of DTLD/DTPS was 1.032± 0.006 and 1.029 ± 0.016 for 6 MV and 10 MV beams. The dose verification for TPS was successfully commenced to check dosimetric data related to a radiotherapy treatment unit equipped with MLC. The recommendation was to extend the postal dosimetry audit to the national scale to improve treatment accuracy.